HIV serostatus disclosure: development and validation of indicators considering target and modality. Results from a community-based research in 5 countries. (December 2015) - Préau, Marie; Beaulieu-Prévost, Dominic; Henry, Emilie; Bernier, Adeline; Veillette-Bourbeau, Ludivine; Otis, Joanne
Abstract: Rationale: HIV serostatus disclosure is a complex challenge for persons living with HIV (PLHIV). Despite its beneficial effects, it can also lead to stigmatization and rejection. The current lack of multi-dimensional measurement tools impede an in-depth understanding of the dynamic of disclosure. Objective: To develop and validate complex measures of serostatus disclosure. Methods: This international community based research study was performed by joint research teams (researchers/community based organizations (CBO)) in five countries (Democratic Republic of the Congo, Ecuador, Mali, Morocco and Romania). A convenience sample of 1500 people living with HIV (PLHIV) in contact with local CBO were recruited in 2011 (300 in each country). Face-to-face interviews were performed using a 125-item questionnaire covering HIV status disclosure to 23 potential disclosure targets and related issues (including personal history with HIV, people's reaction to disclosure, sexuality). A principal component analysis and a hierarchical cluster analysis were performed, in order to identify the main components of HIV disclosure, create measures and classify participants into profiles. Results: Patterns of disclosure were summarized using two main measures: direct and indirect disclosure. Disclosure to sexual partners, whether steady or not, was different from patterns of disclosure to other targets. Among the participants, three profiles emerged – labelled Restricted disclosure, Mainly indirect disclosure and Mainly direct disclosure, respectively representing 61%, 13% and 26% of the total sample. The profiles were associated with different aspects of PLHIV's lives, including self-efficacy, functional limitations and social exclusion. Patterns varied across the five studied countries. Conclusion: Results suggest that multi-dimensional constructs should be used to measure disclosure in order to improve understanding of the disclosure process. Highlights: "Partages" is an international community-based participatory study. Serostatus disclosure is a central topic in HIV-related research. Using a PCA-based approach, we developed measures considering target and modality. We identified three main disclosure profiles using hierarchical cluster analysis. Country-specific patterns of disclosure profiles appeared.